Dark enlightenment : the historical, sociological, and discursive contexts of contemporary esoteric magic - Granholm, Kennet, 1977- (Aries book series. Texts and studies in Western esotericism, 2014)
In Dark Enlightenment Kennet Granholm provides a detailed look at the Left-Hand Path magic order Dragon Rouge in particular and explores the contexts of contemporary esoteric magic in general.